Analisis Kinerja Aparatur Sipil Negara dalam Pelayanan Administratif di Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Bone Bolango Tahun 2025 - Sri Fadhilla Astuti Bouti; Sri Yulianty Mozin; Raihan A. Hanasi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to analyze the performance of the State Civil Apparatus (ASN) in administrative services at the Secretariat of the Regional House of Representatives (DPRD) of Bone Bolango Regency in 2025. The study focuses on addressing five main performance indicators: work quality, work quantity, timeliness, initiative, and work capability. The study employed a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The informants were determined purposively; ASN was directly involved in administrative services. The study’s findings indicate that ASN's performance in administrative services has not been optimal. This is reflected in delays in completing tasks, low discipline in attendance and punctuality, and an unequal distribution of workload among employees. Factors such as work motivation, work environment, organizational culture, and work systems also influence ASN performance. This study concludes that improving ASN performance in administrative services requires comprehensive reforms, including enhancing human resource competencies, optimizing the use of information technology, improving internal communication systems, and organizing a more equitable workload distribution. Therefore, it is expected that the quality of administrative services at the DPRD Secretariat of Bone Bolango Regency will become more effective, efficient, and professional.